KEADAAN SANITASI LINGKUNGAN BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA UPT PUSKESMAS KINTAMANI VI BANGLI - Baskara, Ida Bagus Gede; Sudiadnyana, I Wayan (Poltekkes Kemenkes Denpasar, 2024)
Stunting is a growth disorder in children as a result of chronic malnutrition. Nutritional problems are closely related to environmental factors. Poor sanitation can cause diarrhea in toddlers and impaired absorption of nutrients. The purpose of this study was to determine the relationship between environmental sanitation and the incidence of stunting in toddlers. The research design used analytical observation with a case control approach. The research sample was the total population, namely all toddlers who experienced stunting in November 2023, totaling 97 people and the control was toddlers who were not stunted, totaling 97 people. The results of the study in the case group who had poor sanitation were 80 people (82.5%), and good sanitation were 17 people (17.5%). In the control group, there were 9 people (9.3%) with poor sanitation, and 88 people (90.7%) with good sanitation. The results of the statistical test using Chi Square obtained a p value = 0.000. Thus, there is a relationship between environmental sanitation and the incidence of stunting in the Kintamani VI Health Center Technical Implementation Unit. It is recommended that residents pay more attention to environmental sanitation, especially the physical quality of water sources, waste sorting, management and ownership of toilets.